2016
DOI: 10.1177/0300060515611536
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of diagnosis and management of axial spondyloarthritis in North Africa and the Middle East: An expert consensus

Abstract: Axial spondyloarthritis (SpA) is a spectrum of inflammatory disease with stages characterized by both nonradiographic and radiographic sacroiliitis. Nonradiographic axial SpA is associated with health-related quality-of-life impairment and may progress to ankylosing spondylitis. Axial SpA has a low prevalence in some countries in North Africa and the Middle East, and pooling of data and resources is needed to increase understanding of the regional picture. Early diagnosis and effective treatment are required t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 64 publications
2
27
0
1
Order By: Relevance
“…However, these data should be interpreted with caution, as they are based on very low numbers of patients with data available (six from Northwest Africa and two from South Africa). Although MRI facilities are widely available in Algerian, Moroccan, and South African hospitals, access to these facilities is limited for some patients and this may have contributed to the low numbers [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these data should be interpreted with caution, as they are based on very low numbers of patients with data available (six from Northwest Africa and two from South Africa). Although MRI facilities are widely available in Algerian, Moroccan, and South African hospitals, access to these facilities is limited for some patients and this may have contributed to the low numbers [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from a multinational, noninterventional, cross-sectional, epidemiologic study revealed significant variations across the globe in the prevalence of nr-axSpA among patients with IBP, with the highest prevalence reported in Asia (36.5%) and the lowest reported in Africa (16.0%) [ 11 ]. However, there is limited information on the prevalence and clinical characteristics of nr-axSpA among patients with IBP in individual African countries [ 12 ]. Understanding the prevalence of nr-axSpA in the various regions of Africa and the challenges involved in obtaining this information will provide a foundation for regional rheumatologists and public health agencies to develop programs for early detection and treatment of this disease in their countries.…”
Section: Introductionmentioning
confidence: 99%
“…Primary care physicians sometimes have a limited knowledge of axSpA, leading to a lag time in the referral of patients with low back pain to a rheumatologist. 31 Awareness of nr-axSpA, in particular, is low. 31 Patients are often managed with NSAIDs…”
Section: Physician-related Factorsmentioning
confidence: 99%
“…7 Insurance and/or healthcare policies may affect the speed of diagnosis of axSpA. 31 In the private sector, self-pay patients may experience delays due to the expense of physician visits, laboratory and imaging resources, and medications.…”
Section: Healthcare-related Factorsmentioning
confidence: 99%
“…13 In North Africa and the Middle East, experts tend to use the ASAS/EULAR recommendations for the management of axial SpA. 14 The ASAS/EULAR international recommendations state that bDMARDs should be considered in patients with persistently high disease activity despite conventional treatments, with TNFi therapy being the current treatment standard. 2 In Kuwait, approved treatments for SpA include nonsteroidal anti-inflammatory drugs (NSAIDs) essentially for pain relief, conventional DMARDs (csDMARDs), bDMARDs such as TNFis, and tsDMARDs such as JAKi, for SpA subtypes such as PsA (Table 1).…”
Section: International Guidelines and Recommendationsmentioning
confidence: 99%